2007
DOI: 10.4049/jimmunol.179.4.2223
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipase Cβ Is Critical for T Cell Chemotaxis

Abstract: Chemokines acting through G protein-coupled receptors play an essential role in the immune response. PI3K and phospholipase C (PLC) are distinct signaling molecules that have been proposed in the regulation of chemokine-mediated cell migration. Studies with knockout mice have demonstrated a critical role for PI3K in Gαi protein-coupled receptor-mediated neutrophil and lymphocyte chemotaxis. Although PLCβ is not essential for the chemotactic response of neutrophils, its role in lymphocyte migration has not been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 49 publications
(30 reference statements)
2
55
2
Order By: Relevance
“…Increased expression of p-Smad2/3 in ColVII-null cells suggests activation of the Smad pathway, which is possibly linked to the CXCL10-CXCR3 pathway. CXCRs can act through PLC-β proteins to increase cell movement (Bach et al, 2007), which could explain the increase in PLC-β4 expression observed in ColVII-null SCC cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased expression of p-Smad2/3 in ColVII-null cells suggests activation of the Smad pathway, which is possibly linked to the CXCL10-CXCR3 pathway. CXCRs can act through PLC-β proteins to increase cell movement (Bach et al, 2007), which could explain the increase in PLC-β4 expression observed in ColVII-null SCC cells.…”
Section: Discussionmentioning
confidence: 99%
“…8A). Chemokine receptors (CXCRs) can generate lipidderived second messengers through PLC activation, leading to a rise in intracellular calcium and subsequent directional movement of cells (Bach et al, 2007). Expression of CXCL10, its receptor CXCR3, and PLC-β4 was examined in siCOL7 and siC cells by performing IF staining on sections of collagen:matrigel gels.…”
Section: Loss Of Colvii In Scc Increases Expression Of the Chemokine mentioning
confidence: 99%
“…By contrast, PLC-␤ is clearly necessary for T-cell chemotaxis. It acts by transiently raising cytoplasmic Ca 2+ concentrations via inositol (1,4,5)-trisphosphate [Ins(1,4,5)P 3 , IP3] but does not influence PKC activity (Bach et al, 2007;Smit et al, 2003). The identities of the Ca 2+ -dependent downstream components (such as calmodulin kinases, myosin light-chain kinase or Rho kinase) that mediate the chemotactic response in Tcells remain elusive.…”
Section: Plc and Pld In Mammalian Chemotaxismentioning
confidence: 99%
“…For F, transfected cells were incubated without or with latrunculin A, EGTA, U73343, or U73122 in the absence of SDF-1. FRET images were acquired on fixed cells using acceptor photobleaching as described in the legend of have been implicated in T-cell migration (15,16). In none of these studies has the role of calcium and PLC in T-cell polarization and flotillin capping been addressed.…”
Section: Volume 287 • Number 47 • November 16 2012mentioning
confidence: 99%